Postnatal onset of retinal degeneration by loss of embryonic Ezh2 repression of Six1 - Yan, Naihong; Cheng, Lin; Cho, Kinsang; Malik, Muhammad Taimur A.; Xiao, Lirong; Guo, Chenying; Yu, Honghua; Zhu, Ruilin; Rao, Rajesh C.; Chen, Dong Feng (Scientific reports, 2016)
Some adult-onset disorders may be linked to dysregulated embryonic development, yet the mechanisms underlying this association remain poorly understood. Congenital retinal degenerative diseases are blinding disorders characterized by postnatal degeneration of photoreceptors, and affect nearly 2 million individuals worldwide, but ∼50% do not have a known mutation, implicating contributions of epigenetic factors. We found that embryonic deletion of the histone methyltransferase (HMT) Ezh2 from all retinal progenitors resulted in progressive photoreceptor degeneration throughout postnatal life, via derepression of fetal expression of Six1 and its targets. Forced expression of Six1 in the postnatal retina was sufficient to induce photoreceptor degeneration. Ezh2 , although enriched in the embryonic retina, was not present in the mature retina; these data reveal an Ezh2 -mediated feed-forward pathway that is required for maintaining photoreceptor homeostasis in the adult and suggest novel targets for retinal degeneration therapy.